2017
DOI: 10.1017/s1368980017000738
|View full text |Cite
|
Sign up to set email alerts
|

How Latina mothers navigate a ‘food swamp’ to feed their children: a photovoice approach

Abstract: These mothers' feeding choices were influenced directly by their food values, and indirectly by the neighbourhood and school food environments via their children's preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 63 publications
5
32
0
Order By: Relevance
“…We examined multiple ways of categorizing food environments as food swamps, including alternate versions of the Retail Food Environment Index (RFEI) [ 23 , 34 , 39 ]. This builds upon previous work by Colón-Ramos and colleagues, which employed a relative food environment measure to identify a food swamp in the District of Columbia and predict food acquisition behaviors among recently migrated mothers from Central America [ 35 ]. The other studies that have used relative measures of food access were conducted outside the US, in Waterloo, Canada [ 33 ] and Porirua, New Zealand [ 34 ].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…We examined multiple ways of categorizing food environments as food swamps, including alternate versions of the Retail Food Environment Index (RFEI) [ 23 , 34 , 39 ]. This builds upon previous work by Colón-Ramos and colleagues, which employed a relative food environment measure to identify a food swamp in the District of Columbia and predict food acquisition behaviors among recently migrated mothers from Central America [ 35 ]. The other studies that have used relative measures of food access were conducted outside the US, in Waterloo, Canada [ 33 ] and Porirua, New Zealand [ 34 ].…”
Section: Introductionmentioning
confidence: 89%
“…First, the present study makes a novel contribution by examining the countrywide existence of “food swamps” in the U.S. This builds upon previous work on food swamps abroad [ 33 , 34 ] and studies identifying food swamps in two major U.S. cities [ 21 , 35 ]. For instance, Hager and colleagues identified food swamps as areas in Baltimore City, with four or more convenience/corner stores within 0.25 miles of a study participant’s home.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most research has focused on food purchased for at-home consumption, despite evidence that access to fast food 4 or other non-retail sites may also play significant roles 5 . Furthermore, work on food access has often neglected individuals' everyday food procurement habits 6 and the temporally variable nature of food access, including factors such as store operating hours 7 . At a broader level, a focus on mapping and labelling areas with poor food access may both stigmatize already marginalized communities and distract from more systemic issues such as retailer consolidation and neighbourhood disinvestment 8 .…”
Section: Jerry Shannonmentioning
confidence: 99%
“…Likewise, several studies revealed that health affected mothers' food choice of mothers from, for example, Canada (Walsh et al, 2015), the USA (Johnson et al, 2011), Uruguay (Machín et al, 2016), Senegal (Zobrist et al, 2018) and the UK (Carnell et al, 2011). Moreover, mothers from the USA (Evans et al, 2011;Meers et al, 2016;Colón-Ramos et al, 2017), Indonesia (Rachmi et al, 2018), Australia (Russel et al, 2015Boak et al, 2016) and the UK (Carnell et al, 2011) reported child preference to be important in food choice for their children. However, some considerations seem to be culture-specific, like convenience for Dutch mothers and organic for Polish mothers, which was also found by Markovina et al (2015).…”
Section: Considerations and Value Conflicts In Snack Choicementioning
confidence: 99%